INVESTIGATION OF A PATCHOULI LEAF EMULSION GEL FOR POTENTIAL ACNE TREATMENT - Wei, Li (Ayden Journal of Drug and Pharmaceutical Research, 2024)
Acne is a prevalent skin condition characterized by various manifestations, including seborrhea, blackheads, pinheads, pimples, nodules, and sometimes, tissue grating. It can present in both inflammatory and non-inflammatory forms. The development of acne is multifactorial, involving hormonal imbalances, dietary influences, stress, and inadequate skin hygiene. These factors contribute to an increased production of sebum, blockage of hair follicles, and colonization by acne-causing bacteria, such as Propionibacterium acnes and Staphylococcus epidermidis. Propionibacterium acnes is a normal flora on the human skin, primarily residing in sebaceous glands. The pathogenic mechanism of acne associated with this bacterium involves the production of lipases, which hydrolyze free fatty acids from skin lipids. The interaction of these fatty acids with the immune system triggers tissue inflammation and, consequently, acne formation. Understanding the intricate interplay between these factors and the role of bacteria like Propionibacterium acnes in acne pathogenesis is essential for effective management and treatment of this common skin condition. This knowledge can guide the development of targeted therapies and improved skincare practices.